Enhanced thermal performance in solar receiver duct with louver-punched V-type winglets: Numerical and experimental study - Maturose Suchatawat; Somchai Sripattanapipat; Pitak Promthaisong; Sompol Skullong; Pongjet Promvonge (Results in Engineering)
An experimental and computational research was performed to explore the augmentation of turbulent convection in a solar receiver channel by utilizing louver-punched V-type winglets (LPVWs) that were fixed to the absorber plate. The simulation utilized the realizable k-ε turbulent model, and the predicated outputs were verified by the relevant measured data. At a fixed attack angle (α) of 45°, the LPVW components were mounted on the absorber with the V-tip facing downstream. Using the LPVW, the newly developed absorber is intended to boost thermal performance by generating multiple flows of longitudinal vortices that induce impinging air streams onto the absorber, thereby enhancing heat transmission. The louvered hole on the winglet serves to reduce pressure loss while preserving the primary vortices. In the current investigation, the winglet parameters consisted of a single relative winglet height (BR = 0.4), four louver size ratios (RL = e1/b = 0.9, 0.7, 0.5, and 0.3), and five louver-flapped angles (β = 90°, 60°, 45°, 30°, and 0°). The LPVW with β > 0° substantially reduced the solid-winglet (β = 0°) friction loss, whereas the heat transmission was slightly declined, as indicated by the results. The solid winglet (β = 0°) exhibited the largest frictional loss and heat transmission, with values approximately 6.3 and 48.2 times the smooth flat duct, respectively. The optimal performance of the LPVW was roughly 2.58, at RL = 0.9 and β = 45° Furthermore, empirical correlations for heat transmission and frictional loss were established for this solar receiver duct system. To investigate the heat transmission and flow patterns, a 3-dimensional numerical simulation was implemented, and the predictions were verified against the measured data. The findings were in good accord between the numerical and measured data. For greater thermal performance, the LPVW is reconfigured by altering the locations of the louver holes. The revised LPVW exhibits a peak TEF of 2.7 at β = 35°, l2/l1 = 0.15, l3/l1 = -0.15 and RL = 0.9, about 4.65 % superior than the initial analysis.